Respuesta :
Step 3. Because what you do to one side you have to do to the other. So step 3: 3x-2+2=6+2. :) hope this helps
Answer:
Step 3 was made error because 2 is not added to the right side of the equation.
Step-by-step explanation:
Here, the given expression is,
7x − one over two (8x + 4) = 6
⇒ [tex]7x-\frac{1}{2}(8x+4)=6[/tex]
So, the steps which are involved in solving the given equation are as follows,
Step 1 : By distributive property,
[tex]7x-4x-2=6[/tex]
Step 2 : Combine like terms,
[tex]3x-2=6[/tex]
Step 3 : Adding 2 on both sides,
[tex]3x-2+2=6+2[/tex]
Step 4 : Combine like terms,
[tex]3x=8[/tex]
Step 5 : By division property of equality,
[tex]x=\frac{8}{3}[/tex]
Thus, by the above explanation it is clear that step 3 was made error because 2 is not added to the right side of the equation.